2019
DOI: 10.1098/rspb.2019.1828
|View full text |Cite
|
Sign up to set email alerts
|

Loss of olfaction in sea snakes provides new perspectives on the aquatic adaptation of amniotes

Abstract: Marine amniotes, a polyphyletic group, provide an excellent opportunity for studying convergent evolution. Their sense of smell tends to degenerate, but this process has not been explored by comparing fully aquatic species with their amphibious relatives in an evolutionary context. Here, we sequenced the genomes of fully aquatic and amphibious sea snakes and identified repertoires of chemosensory receptor genes involved in olfaction. Snakes possess large numbers of the olfactory receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 74 publications
(126 reference statements)
1
26
0
Order By: Relevance
“…1). Our observation of repeated reduction of olfactory surface area is also consistent with convergent enrichment in pseudogenes as well as reduction of the number of functional OR genes in amphibious and aquatic vertebrate genomes (26)(27)(28)(29)(30)(31)39). We demonstrated that small amphibious mammals convergently lost a part of their olfactory capacities.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…1). Our observation of repeated reduction of olfactory surface area is also consistent with convergent enrichment in pseudogenes as well as reduction of the number of functional OR genes in amphibious and aquatic vertebrate genomes (26)(27)(28)(29)(30)(31)39). We demonstrated that small amphibious mammals convergently lost a part of their olfactory capacities.…”
Section: Discussionsupporting
confidence: 84%
“…olfactory bulb and cribriform plate, two components of olfaction, compared to their terrestrial relatives (24)(25)(26). Aquatic vertebrates also have a smaller repertoire of functional olfactory receptor (OR) genes than terrestrial vertebrates (27)(28)(29)(30)(31)(32). Nevertheless, how pervasive, consistent, and strong these putative convergences and trade-offs are remains unknown.…”
Section: Significancementioning
confidence: 99%
“…1990 ; Camacho et al. 2009 ) to perform a nucleotide search for the consensus sequences of each subfamily in the genomes of two closely related terrestrial elapids ( N. scutatus and P. textilis ) (provided by Richard Edwards), and a more distantly related semi-marine elapid ( L. colubrina ) ( Kishida et al. 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the search of closely related terrestrial species, we used megablast to perform reciprocal searches for the consensus sequences of the seven Aipysurus LINE subfamilies in the genomes of H. melanocephalus and Emydocephalus annulatus ( Kishida 2019 ), and assembled transcriptomes from various tissues of A. laevis , A. tenuis , and H. major from Crowe-Riddell et al. (2019) .…”
Section: Methodsmentioning
confidence: 99%
“…Aquatic habitats largely eliminate substrate-deposited chemical trails, promoting reliance on other types of cues (such as visual ones [17]). However, many marine organisms (including fish) produce waterborne chemicals that may be detectable by a snake's highly specialized vomeronasal system [18,19], and three species of sea snakes have been reported to use chemical cues from their prey to select foraging sites (Emydocephalus annulatus [20]; Hydrophis melanocephalus and H. ornatus [21]. Thus, although the threedimensional nature of the aquatic environment reduces the usefulness of substrate-deposited cues, it allows other kinds of chemical cues to be widely disseminated.…”
Section: Introductionmentioning
confidence: 99%